UJI NILAI KALOR BRIKET CAMPURAN KAYU POHON ASAM, KOTORAN SAPI DAN SERBUK GERGAJI SEBAGAI PENGGANTI BAHAN BAKAR ALTERNATIF - Wahyuna, Sri; Said L, Muh; Hernawati, Hernawati (JFT : Jurnal Fisika dan Terapannya, 2015)
The purpose of this study is how the calorific value of wood briquettes mix Tamarind Tree, cow manure and sawdust. In the present study is carried out by varying the material composition of the briquettes and the particle size of 25 mesh material. Then do a calorific power test using a bomb calorimeter. Based on the research results obtained kinds of briquettes that has the highest heating value of wood tamarind material composition: 50 grams, sawdust: 25 grams, cow dung: 10 grams, adhesive materials: 15 grams Â white the calorific value generated 4696.8990 calori / grams. For this type of briquettes with low calorific value, with the composition of the wood used is the acid: 15 grams, sawdust: 15 grams of cow dung: 35 grams, and sawdust: 35 grams. The calorific value is generated is equal to 3174, 7376 calori/ grams.